2020
DOI: 10.33542/gc2020-1-05
|View full text |Cite
|
Sign up to set email alerts
|

Thermal data analysis for urban climate research: A case study of Olomouc, Czechia

Abstract: Due to the recent advancements in thermal camera technology, it is easier than ever to acquire information about surface temperature in very-high or extreme spatial resolution from manned or unmanned airborne vehicles. The main objective of the paper is to investigate the possibilities of extreme resolution thermal data for urban climate research. The main dataset used for the work is thermal mosaic acquired by an aeroplane above the city of Olomouc in the morning and afternoon on 10 th July 2016. The spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Explicit consideration of the geometric and surface properties, as defined in the definitive LCZ study [33], served to classify the LCZs as fixed measure-ment sites [75], while mobile measurement traverses formed the basis of urban climate research in Cluj-Napoca (Romania) [75] and Uppsala (Sweden) [50]. Pour et al [76] and Pour and Voženílek [77] personally delineated and visualized the most common LCZs in Olomouc (Czech Republic) by combining local expert knowledge and Urban Atlas classification with airborne thermal remote-sensing datasets to assess the thermal regime of a range of urban patterns. An alternative approach, addressing urban thermal and wind modelling, was taken in the definition of ten built-up LCZs in Basel (Switzerland) by Theeuwes et al [78] and Droste et al [79].…”
Section: Expert Knowledge-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicit consideration of the geometric and surface properties, as defined in the definitive LCZ study [33], served to classify the LCZs as fixed measure-ment sites [75], while mobile measurement traverses formed the basis of urban climate research in Cluj-Napoca (Romania) [75] and Uppsala (Sweden) [50]. Pour et al [76] and Pour and Voženílek [77] personally delineated and visualized the most common LCZs in Olomouc (Czech Republic) by combining local expert knowledge and Urban Atlas classification with airborne thermal remote-sensing datasets to assess the thermal regime of a range of urban patterns. An alternative approach, addressing urban thermal and wind modelling, was taken in the definition of ten built-up LCZs in Basel (Switzerland) by Theeuwes et al [78] and Droste et al [79].…”
Section: Expert Knowledge-based Methodsmentioning
confidence: 99%
“…Gholami and Beck [124] determined the relationship between LST and LCZ for 25 cities worldwide, but with only a few examples for European cities. Pour et al [76] and Pour and Voženílek [77] took airborne thermal images (using a thermal camera installed in a light aeroplane) for the city of Olomouc (Czech Republic), and determined that the highest surface temperatures occurred in LCZs 2, 4, 5, and 8. In similar fashion, Skarbit et al [84] analysed LST differences between the LCZs of Szeged on the basis of airborne thermal measurements during the early night hours, and the general results indicated that LCZ 6 has the lowest early nighttime LST compared with other densely built-up LCZs such as LCZs 2, 3, and 5.…”
Section: Thermal Analysis Based On Land-surface Measurementsmentioning
confidence: 99%
“…In cases when in the study area there are different restrictions on measuring the UHI phenomenon, such as the lack of equipment/instruments for measuring temperature and their inhomogeneous distribution (as in our case of the study area), then it is necessary to use GIS and remote sensing techniques (Berila & Dushi, 2021). Using them to measure the UHI phenomenon represents SUHI, which is determined using geospatial technology through the calculation of the land surface temperature (Voogt & Oke, 2003;Despini et al, 2016;Pour & Voženílek, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is evident in cases where the study area has insufficient data on the measured temperaturethe distribution of measuring equipment is inhomogeneous and rare. Thus, the use of geospatial technology emerges as a suitable tool to determine such a phenomenon through the calculation of LST (Land Surface Temperature) (Pour & Voženílek, 2020;Despini et al, 2016;Voogt & Oke, 2003). Atmospheric UHI is called as such by merging BLHI and CLHI.…”
Section: Introductionmentioning
confidence: 99%